Planet 51 [videorecording (DVD)] - Blanco, Jorge; Johnson, Dwayne, 1972-; Biel, Jessica, 1982-; Long, Justin, 1978-; Oldman, Gary; Scott, Seann William; Cleese, John (Sony Pictures Home Entertainment, 2010)
American astronaut Captain Charles T. Baker thinks he is the first person to set foot on Planet 51. Little does he know the planet is inhabited by little green people who live in a cheerful innocent world. The only fear they have is that their planet will be overtaken by alien invaders from planet Earth. Now, before he becomes part of the Planet 51 Alien Invaders Space Museum, Captain Baker, with the help of his new friend, Lem, must figure out a way to escape and return back to Earth.